2012
DOI: 10.1016/j.ijrobp.2011.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Genotype-Dependent Paradoxical Short-Term Effects of 56Fe Irradiation on the Brain

Abstract: Purpose In humans, apolipoprotein E (apoE) is encoded by three major alleles (ε2, ε3, and ε4) and, compared to apoE3, apoE4 increases the risk of developing Alzheimer disease and cognitive impairments following various environmental challenges. Exposure to irradiation, including that of 56Fe, during space missions poses a significant risk to the central nervous system, and apoE isoform might modulate this risk. Methods and Materials We investigated whether apoE isoform modulates hippocampus-dependent cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…A dissociation between cognitive performance in the water maze and contextual learning in fear conditioning was previously reported [38, 39]. Consistent with the current study, whole-body high-LET irradiation affected water maze performance, but not contextual fear conditioning within one month following radiation exposure in human apoE mice [40] or 13 months following high LET irradiation [41]. These data emphasized the importance of including different hippocampus-dependent cognitive tests in assessing effects of irradiation on the brain.…”
Section: Discussionsupporting
confidence: 91%
“…A dissociation between cognitive performance in the water maze and contextual learning in fear conditioning was previously reported [38, 39]. Consistent with the current study, whole-body high-LET irradiation affected water maze performance, but not contextual fear conditioning within one month following radiation exposure in human apoE mice [40] or 13 months following high LET irradiation [41]. These data emphasized the importance of including different hippocampus-dependent cognitive tests in assessing effects of irradiation on the brain.…”
Section: Discussionsupporting
confidence: 91%
“…The age at evaluation and irradiation affects the responses to charged particles (Rabin et al 2012) and X-rays (Forbes et al 2014). Sex and genotype (e.g., ApoE allele and ATM) are important variables (Acevedo et al 2008;Benice and Raber 2009;Haley et al 2012;Higuchi et al 2002;Villasana et al 2006Villasana et al , 2011Yamamoto et al 2011;Yeiser et al 2013;Johnson et al 2014;Parihar et al 2014). Additionally, observations comparing head only-, body only-, or whole body-irradiated animals demonstrate a significant role for the periphery in determining behavioral responses .…”
Section: Behavioral Effects a Overall Observationsmentioning
confidence: 99%
“…Manda et al showed that 56 Fe (1.5 Gy at 500 MeV/n) increased the time male wild-type mice needed to locate the hidden platform in the water maze 30 days following irradiation but not at earlier time points [19, 20]. Recently, we showed early cognitive effects two weeks following 56 Fe irradiation in wild-type (0.1 Gy at 500 MeV/n)[21] and human apoE mice (0.5 Gy at 500 MeV/n) [22]. …”
Section: Introductionmentioning
confidence: 99%